EFFECTS OF ARBUSCULAR MYCORRHIZA AND PHOSPHORUS APPLICATION ON GROWTH AND COLCHICINE CONCENTRATION IN GLORIOSA SUPERBA. - Pandey, D.; Banik, Rathindra Mohan (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Gloriosa superba produces an array of alkaloids including colchicine, a compound of current interest in the treatment of various diseases. The tuber of Gloriosa superba is a rich source of colchicine which has shown anti-gout, anti-inflammatory, and antitumor activity. However, this promising compound remains expensive and Gloriosa superba is good source in global scale. Increase in yield of naturally occurring colchicine is an important area of investigation. The effects of inoculation by four arbuscular mycorrhizal (AM) fungi, Glomus mossae, Glomus fasciculatum, Gigaspora margarita and Gigaspora gilmorei either alone or supplemented with P-fertilizer, on colchicine concentration in Gloriosa superba were studied. The concentration of colchicine was determined by high-performance thin layer chromatography. The four fungi significantly increased concentration of colchicine in the herb. Although there was significant increase in concentration of colchicine in nonmycorrhizal P-fertilized plants as compared to control, the extent of the increase was less compared to mycorrhizal plants grown with or without P-fertilization. This suggests that the increase in colchicine concentration may not be entirely attributed to enhanced P-nutrition and improved growth. Among the four AM fungi Glomus mossae was found to be best. The study suggests a potential role of AM fungi in improving the concentration of colchicine in Gloriosa superba tuber.